Role of protease-activated receptor 1 in tumor metastasis promoted by tissue factor - Bromberg, M E; Bailly, M A; Konigsberg, W H (Thrombosis and haemostasis, 2001)
Tissue factor (TF) is a transmembrane glycoprotein that complexes with factor VIIa to initiate blood coagulation. We previously reported that expression of high levels of TF in a human melanoma cell line promotes metastasis. Both the cytoplasmic domain of TF and its extracellular domain complexed with factor VIIa are required for the metastatic effect. To further explore the mechanism of TF-mediated metastasis, we investigated the possibility that a protease-activated receptor (PAR) might play a role. For this purpose, we first determined the expression levels of the known PARs (PAR1-4) in a human melanoma cell line, SIT1, that has low endogenous levels of TF and low metastatic potential. We found negligible levels of all of the known PARs and transfection of this cell line with human TF cDNA did not alter expression of the known PARs. To study the possible role of PAR1 in TF-mediated metastasis, we prepared a panel of transfected cell lines with varying levels of TF and PAR1. Our studies show that TF promotes metastasis by a pathway that does not involve high expression of known PARs by tumor cells. In addition, while overexpression of PAR1 is insufficient to induce metastasis in cells with low TF expression, it enhances the metastatic potential of cells with high TF expression, indicating a possible synergy between TF and PAR1 in promoting metastasis.